2014
DOI: 10.1007/s10339-014-0637-x
|View full text |Cite
|
Sign up to set email alerts
|

Zazen meditation and no-task resting EEG compared with LORETA intracortical source localization

Abstract: Meditation is a self-induced and willfully initiated practice that alters the state of consciousness. The meditation practice of Zazen, like many other meditation practices, aims at disregarding intrusive thoughts while controlling body posture. It is an open monitoring meditation characterized by detached moment-to-moment awareness and reduced conceptual thinking and self-reference. Which brain areas differ in electric activity during Zazen compared to task-free resting? Since scalp electroencephalography (EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 82 publications
(92 reference statements)
8
33
1
4
Order By: Relevance
“…It is also noteworthy that no significant changes in any of the other frequency bands were discovered over the course of the meditation, either within-or between-groups, which is in contrast to a number of previous studies which have utilized eyes-closed meditation techniques (Aftanas & Golocheikine, 2001, 2002, 2003Cahn & Polich, 2006;Faber et al, 2014;Huang & Lo, 2009;Lagopoulos et al, 2009). In particular the absence of changes related to the gamma frequency band is different from studies using eyes closed meditation.…”
Section: Meg Study Of Eyes-open Mindfulness Meditation In Long-term Mcontrasting
confidence: 72%
See 1 more Smart Citation
“…It is also noteworthy that no significant changes in any of the other frequency bands were discovered over the course of the meditation, either within-or between-groups, which is in contrast to a number of previous studies which have utilized eyes-closed meditation techniques (Aftanas & Golocheikine, 2001, 2002, 2003Cahn & Polich, 2006;Faber et al, 2014;Huang & Lo, 2009;Lagopoulos et al, 2009). In particular the absence of changes related to the gamma frequency band is different from studies using eyes closed meditation.…”
Section: Meg Study Of Eyes-open Mindfulness Meditation In Long-term Mcontrasting
confidence: 72%
“…Consistent with the eyes-closed meditation literature, an early EEG study by Murata et al (1994) involving 20 Zen monks and 10 control participants reported that frontal theta power was significantly increased 25 minutes into eyes-open meditation in comparison to the start of meditation, an increase that was only observed in the monks. In a more recent EEG study by Faber et al (2014), changes in brain activity were investigated in 15 experienced Zen practitioners whilst they completed 60 minutes of eyes-open meditation versus no-task resting, with the data analysed using low resolution brain electromagnetic tomography (LORETA). In comparison to the rest condition, alpha-1 (8.5-10 Hz) and alpha-2 (10.5-12 Hz) activity were found to be significantly increased in a right-lateralized cluster which included prefrontal areas, insula, somatosensory, motor cortices and temporal areas.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Not only does meditation facilitate the ability to remain calm and in control of emotions during stressful situations, it also helps one to gain a better understanding of one's 'self' or presence in reality [52]. Meditation may be thought of as a voluntary practice altering state of mind in the direction of pure consciousness [53]. The process of meditation activates the brain's prefrontal cortex (PFC) increasing levels of free glutamate in the brain [50,54].…”
Section: Experiencing the 'Self' Through Meditationmentioning
confidence: 99%
“…EEGs have shown that the 'breath of fire' technique that requires a moderate amount of conscious control, results in increased heart rate and decreases the connection between heart rate and breathing [63], that again are different experiences from pure consciousness. Zazen practitioners focus on attention on detachment from the thinking process to minimize thoughts, which has been shown to "enhance automatic memory, emotion processing, reduce conceptual thinking, and reduce judgmental self-referencing," along with "health, well-being and happiness" [53,64].…”
Section: Experiencing the 'Self' Through Meditationmentioning
confidence: 99%
See 1 more Smart Citation